Cognitive development of child as condition of his personal development - E I Komkova (RUDN Journal of Psychology and Pedagogics, 2010)
The results of cognitive and personal development of children till 4-5 until 17-18 age presented in the article, disclosing the concept cognitive-personal development of child on the basic ontogenesis stages on the base of proved empirical research.